THE EFFECT OF ESSENTIAL OIL MIXTURES ON MORTALITIES AND OVIPOSITION DETERRENTS OF Crocidolomia pavonana AND Helopeltis antonii - Tri Lestari Mardiningsih; Rodiah Balfas (Buletin Penelitian Tanaman Rempah dan Obat, 2017)
Essential oil, such as citronella, lemongrass, ageratum, and clove are known to be toxic and repel certain pests. Mixing two or more essential oils are expected increasing their insecticidal properties.  The experiments aimed to examine the effect of essential oils mixtures (EOs) on mortalities and oviposition deterrents of Crocidolomia pavonana and Helopeltis antonii. The experiments were conducted at the laboratory and green house of the Indonesian Spices and Medicinal Crops Research Institute. The tested mixtures were citronella and clove (CiC); lemongrass and clove (LC); ageratum and clove (AC); individual EO; control 1 (water + emulsifier); control 2 (water) at 0.5% concentration for all treatments. The ratio used were 1:1, 1:2, 1:4, 2:1 and 4:1. Parameters observed were the mortalities of C. pavonana larvae and H. antonii nymphs; and the ovipositions deterrents of both insects. The CiC and LC mixtures gave low mortality (<50%) to C. pavonana larvae, while AC at ratios 1:1, 1:2,1:4 less than 20%, AC 2:1 and 4:1 >60% and the individual ageratum oil caused 77.5% mortalities. The CiC 1:1 and LC (1:1, 1:2, and 4:1) showed >40% mortalities of     H. antonii, whereas the AC in all ratios enhanced the nymph mortalities. The number of eggs laid by C. pavonana at CiC and LC in all ratios were around 50-60% lower than individual EO. The mixture of AC 1:4 and 4:1 produced eggs nearly 50% lower than clove treatment. The CiC and LC at 1:1 produced the lowest numbers of egg laid by H. antonii, while AC 1:4 reduced 70% eggs laid compared to individual EO.